1998
DOI: 10.1093/emboj/17.2.615
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the intracellular stability and toxicity of diphtheria toxin through degradation by the N-end rule pathway

Abstract: The enzymatically active A-fragment of diphtheria toxin enters the cytosol of sensitive cells where it inhibits protein synthesis by inactivating elongation factor 2 (EF-2). We have constructed a number of diphtheria toxin mutants that are degraded by the Nend rule pathway in Vero cells, and that display a wide range of intracellular stabilities. The degradation could be inhibited by the proteasome inhibitor lactacystin, indicating that the proteasome is responsible for Nend rule-mediated degradation in mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 62 publications
5
32
0
1
Order By: Relevance
“…However, the only known functions of LLO and the phospholipases are required in vacuoles, where presumably they would be protected from degradation via the N-end rule pathway. Recently, in a study similar to the one presented here, it was shown that diphtheria toxin is degraded by the N-end rule pathway of eukaryotic cells (Falnes and Olsnes, 1998). Moreover, it was demonstrated that the half-life of this toxin, whose site of action is in the host cell cytosol, corresponds to its degree of toxicity in Vero cells.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, the only known functions of LLO and the phospholipases are required in vacuoles, where presumably they would be protected from degradation via the N-end rule pathway. Recently, in a study similar to the one presented here, it was shown that diphtheria toxin is degraded by the N-end rule pathway of eukaryotic cells (Falnes and Olsnes, 1998). Moreover, it was demonstrated that the half-life of this toxin, whose site of action is in the host cell cytosol, corresponds to its degree of toxicity in Vero cells.…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, it was demonstrated that the half-life of this toxin, whose site of action is in the host cell cytosol, corresponds to its degree of toxicity in Vero cells. The results of the present study and that of Falnes and Olsnes (1998) suggest that there is a general relationship between subcellular location, half-life and function of virulenceassociated proteins, a possibility that warrants further investigation. In summary, we have shown that the N-terminus of an intracellular bacterial protein can in¯uence its degradation rate and, consequently, its function.…”
Section: Discussionsupporting
confidence: 51%
“…Indeed, protease inhibitors are known to increase the cytotoxicity of other protein cytotoxins (57). Similarly, the addition of proteolytic degradation signals can decrease protein cytotoxicity (58). Finally, it is noteworthy that protein toxins such as diphtheria toxin, enterotoxin, and abrin II have T m values near that of RNase A (59 -61).…”
Section: Discussionmentioning
confidence: 99%
“…The delay in apoptosis to 48-60 h corresponds with the time required for toxin internalization, translocation and EF2 inactivation. 30 Mutation of the p53 gene and loss of its function is frequently observed in acute phase CML. 31 Mutant p53 cells have poor apoptosis induction by conventional cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%